The Negative Effect of Gadget on Students’ Physical Fitness - Mujahid, Anwar; Handayani, Widya; Imansyah, Farizal (Journal of Social Work and Science Education, 2023)
Many school students still need attention regarding physical activity, either when participating in learning PJOK or other physical activities, a decrease in the level of physical activity of students is observed. This research is descriptive quantitative research. The population in this study was 40 people. The sample in this research was 40 people. Based on the results of the study, it can be seen that the results of the study are visible. The conclusion of this study shows that the rate of use of gadgets in the frequent category is 70.00% and vice versa, the level of physical in the category is well dominated by the fitness of children. this shows that if the use of Gadgets is more controlled and redirected to physical activities that children like, this will further improve children's physical fitness in performing various activities. Gadgets can be addictive in children, so parents and teachers should focus on providing control over children so that the use of gadgets/smartphones can be reduced so as not to affect the child's social activities, including sports. although in this case, aids are not the main factor hindering children in sports activities.